(untitled) (Global Journal of Medical Research, 2023)
Introduction and objective The intestinal neuroendocrine tumor is a rare cancer with incidence of 1-2 100 000 inhabitants Most cases are asymptomatic and late diagnosed The aim of this work is to present a rare neuroendocrine intestinal tumor case in the distal ileum well-differentiated with nonspecific and characteristic disease symptoms Case presentation 56-year-old male smoker diagnosed with well-differentiated neuroendocrine neoplasia histological grade 1 G1 located in the terminal ileum after exploratory laparotomy Discussion It is a rare neoplasm that mainly affects the gastrointestinal tract Practically always slow-growing The clinic is nonspecific in most cases and the principal indication is abdominal pain There is great potential for metastasis depending on the tumor size location and histological grade Imaging and laboratory tests can assist in diagnosis The therapy selection depends on the stage and can range from total tumor resection to antitumor chemotherapy